ANALISIS PENGARUH ARSITEKTUR BIOFILIK DAN KONFIGURASI SPASIAL TERHADAP POLA PEMILIHAN RUANG PUBLIK DI UPTOWN MALL BSB CITY SEMARANG - Aji Setiawan; Budi Sudarwanto; Agung Budi ardjono (Tesa Arsitektur, 2026)
Semi-open shopping malls have emerged as commercial spaces that foster stronger connections with nature while responding to visitor behavior. This study examines the relationship between biophilic architecture and spatial configuration in shaping public space selection patterns at Uptown Mall BSB City Semarang. A mixed-method approach was employed through Space Syntax simulation, temperature and wind speed measurements, observation of spatial use  patterns, and interviews with 28 respondents across four observation areas. The findings indicate that strategically accessible areas are not always the most preferred spaces when lacking shading, thermal comfort, natural airflow, and social activities. Conversely, spaces that provide a balance between accessibility, natural atmosphere, and thermal comfort tend to encourage longer user occupancy. The novelty of this study lies in integrating Space Syntax and biophilic principles to analyze spatial selection in semi-open shopping malls. These findings contribute to the development of biophilic-based commercial public space design strategies that are more comfortable, adaptive, and responsive to visitor behavior.